PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PUBLIKASI SUSTAINABILITY REPORT (Studi Empiris pada Perusahaan Indeks KOMPAS 100 di Bursa Efek Indonesia Tahun 2014 s/d 2015) - Dinda Dwipa Racelia; Raja Adri; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the influence of corporate characteristics and corporate governance consisting of corporate activities, company size, liquidity, audit committee and board of directors of sustainability report publication on the company KOMPAS100 Index in Indonesia Stock Exchange 2014 s / d 2015. Data used in this research is secondary data from financial data at Indonesia Stock Exchange. The sample method used is purposive sampling, of the population of 114 companies listed in the KOMPAS 100 Index during the Year 2014 s / d 2015, there are research samples of 27 companies that meet the criteria. Hypothesis testing is done by using logistic regression analysis. The result of the research based on hypothesis test show that company activity, company size, liquidity and board of directors do not have significant influence to the sustainability report publication with significant that is 0402, 0.394, 0,590 and 0,296, while audit committee have significant influence to sustainability report publication with significant 0.012. The magnitude of influence (Nagelkerke R-Square) of corporate characteristics and corporate governance is 34.9% while the remaining 65.1% is influenced by other variables.Keywords : Inventory Turnover, Company Size, Current Ratio, Audit Committee and Board of Directors.